Performance of banana genotypes with resistance to black leaf streak disease in Northeastern Brazil - Weber, Olmar Baller; Garruti, Deborah dos Santos; Norões, Normândia Pereira; Silva, Sebastião de Oliveira e (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the growth and the production of banana plants with resistance to black leaf streak disease (BLSD), in comparison with the performance of traditional cultivars susceptible to the disease. Twenty cultivars were planted at the Jaguaribe-Apodi plateau, in Northeastern Brazil: 15 with resistance to BLSD, namely Pacovan Ken, PV42-68, BRS Vitória, BRS Japira, BRS Preciosa, BRS Garantida, Thap Maeo, BRS Tropical, BRS Platina, BRS Maravilha, FHIA 02, FHIA 18, Galil 18, Caipira, and Buccaneer; and five susceptible to the disease, namely Williams, Grande Naine, Pacovan, Prata Anã, and Maçã. Banana growth and production of bunches were evaluated during three successive cycles. 'BRS Tropical' and 'Caipira' can replace 'Maçã', which is very susceptible to Fusarium wilt. The BRS Maravilha, BRS Platina, FHIA 02, FHIA 18, and Galil 18 cultivars show adequate height and high yield potential, being alternatives to the traditional Prata subgroup. The Buccaneer cultivar is an alternative to the susceptible cultivars of the Cavendish subgroup and can be explored in an irrigated agrosystem.
Keywords: Musa; Mycosphaerella fijiensis; banana cultivars; black leaf streak disease